Powering Goat Milk with Nature: Functional Foods Enriched with Purslane (Portulaca grandiflora) and Probiotics - Djoko Kisworo; Dewi Wulandani Baiq Rani; Bulkaini Baiq Rani; Yulianto Wahid; Fahrullah Baiq Rani; Novizar Nazir (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Abstract Portulaca oleracea (purslane) is a plant rich in bioactive compounds such as flavonoids, polyphenols, and ascorbic acid, which have great potential as functional ingredients in food products. This study aimed to determine the effect of adding purslane extract on the chemical and microbiological characteristics of probiotic ice cream containing Lactobacillus plantarum. The experiment used a Completely Randomized Design (CRD) with four treatments: P0 (0%), P1 (1%), P2 (2%), and P3 (3%) purslane extract, each with three replications. Parameters observed included moisture, fat, fiber, protein, antioxidant activity, pH, and L. plantarum population. Data were analyzed using ANOVA followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level. The results showed that the addition of purslane extract significantly affected fat, fiber, protein, antioxidant activity, and L. plantarum population (p<0.05), but had no significant effect on moisture content and pH. Fiber content increased from 2.21% (P0) to 3.53% (P3), antioxidant activity from 32.86% to 42.10%, and L. plantarum population from 0 to 5.26 log CFU/g, while fat content decreased from 3.45% to 2.41%. The increase in fiber and antioxidant activity indicated that purslane extract enhanced the functional value of ice cream, while the growth of L. plantarum suggested a prebiotic effect of purslane-derived dietary fiber. It can be concluded that the addition of up to 3% purslane extract produced probiotic ice cream with the best chemical and microbiological characteristics, showing strong potential as a natural functional food with health benefits, particularly through enhanced antioxidant activity and probiotic viability.